Rhynchosauroides Footprint Variability in a Muschelkalk Detrital Interval (Late Anisian–Middle Ladinian) from the Catalan Basin (NE Iberian Peninsula). Issue 2 (3rd July 2018) - Mujal, Eudald; Iglesias, Guillem; Oms, Oriol; Fortuny, Josep; Bolet, Arnau; Méndez, Josep Manel
ABSTRACT: The Middle Triassic successions of coastal and distal alluvial systems are often characterized by the presence of the tetrapod ichnotaxon Rhynchosauroides . Nevertheless, few studies paid attention on the paleoenvironmental implications of this widely distributed ichnogenus. The finding of a new Rhynchosauroides -dominated tracksite opens the window to the use of such footprints in paleoenvironmental studies. The tracksite is located in the active quarry of Pedrera de Can Sallent, at Castellar del Vallès (Catalan Basin, NE Iberian Peninsula). The footprints were recovered from the Middle Muschelkalk detrital unit, composed of a claystone-sandstone-gypsum succession from a sabkha setting of late Anisian-middle Ladinian age. This unit was deposited during a short regression interval within the main Middle Triassic transgression represented by the Muschelkalk facies. The ichnoassociation is composed of Rhynchosauroides isp., and a single, partially preserved, undetermined large footprint. Among Rhynchosauroides specimens, three different preservation states were recognized, corresponding to substrates in (1) subaqueous conditions (surfaces with scarce, deformed, and deeply impressed ichnites), (2) occasionally flooded (mostly trampled surfaces, footprints commonly well preserved), and (3) subaerial exposition (surfaces with few footprints, sometimes corresponding to faint impressions or only preserved by claw marks). The footprint morphological variations of Rhynchosauroides are correlated to substrate rheology and further to the environmental conditions. Rhynchosauroides is a characteristic morphotype that often dominates in the Anisian-Ladinian coastal and distal alluvial settings of several European tracksites. Therefore, these ichnoassociations in such environments, awaiting further detailed analyses, may constitute a distinct ichnocoenosis.